1994
DOI: 10.1128/cdli.1.2.206-213.1994
|View full text |Cite
|
Sign up to set email alerts
|

Immunochemical identification of Brucella abortus lipopolysaccharide epitopes

Abstract: Sera from Brucella abortus-infected and -vaccinated bovines recognized four lipopolysaccharide (LPS) determinants: two in the O-polysaccharide (A and C), one in the core oligosaccharide from rough Brucella LPS (R), and one in lipid A (LA). From 46 different hybridomas secreting monoclonal antibodies (MAbs) against various LPS moieties, 9 different specificities were identified. Two epitopes, A and C/Y, were present in the O-polysaccharide. Two epitopes were found in the core oligosaccharide (R1 and R2) of roug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 34 publications
0
33
0
Order By: Relevance
“…The monoclonal antibody (mAb) (Baps C/Y) directed against B. abortus LPS C/Y epitope coupled to peroxidase and antiserum from infected cows were previously described (Rojas et al, 1994). The antiserum from infected cows was used to label Y. enterocolitica 0:9 LPS (same O-chain as B. abortus; for review see Moriyon, 2004).…”
Section: Antibodies and Reagentsmentioning
confidence: 99%
“…The monoclonal antibody (mAb) (Baps C/Y) directed against B. abortus LPS C/Y epitope coupled to peroxidase and antiserum from infected cows were previously described (Rojas et al, 1994). The antiserum from infected cows was used to label Y. enterocolitica 0:9 LPS (same O-chain as B. abortus; for review see Moriyon, 2004).…”
Section: Antibodies and Reagentsmentioning
confidence: 99%
“…For quantification analyses, extracellular bacteria were detected by incubating the cells for 30 min with a serum (diluted 1:10 000 in 10% mouse serum in PBS) from a B. abortus-infected cow (Rojas et al, 1994) and by revealing the antibodies with Texas red-conjugated goat anti-cow IgG antibodies (Immunotech). Intracellular bacteria were detected by permeabilization of cells with 0.05% saponin (Sigma), incubation for 30 min with serum (at 1:5000 in 10% mouse serum in PBS) from a B. abortus-infected rabbit (Rojas et al, 1994) revealed by FITCconjugated donkey anti-rabbit IgG (Immunotech). For confocal studies regarding the intracellular localization of internalized bacteria, two protocols were used.…”
Section: Immunofluorescence and Confocal Fluorescence Microscopymentioning
confidence: 99%
“…The presence of cathepsin D (a well-known marker for lysosomes) was detected with rabbit anti-cathepsin D antibodies (Meresse et al, 1995) revealed by FITC-conjugated donkey anti-rabbit IgG. For triple immunofluorescence analysis, extracellular bacteria were detected by incubating the cells for 30 min with a mouse monoclonal anti-Brucella antibody (diluted 1:100 in 10% horse serum in PBS) (Rojas et al, 1994) revealed by cyanin 5-conjugated donkey anti-mouse IgG (Immunotech). Cells were then permeabilized with 0.05% saponin and intracellular bacteria were detected by incubating cells for 30 min with the cow anti-Brucella serum revealed by Texas red-conjugated goat anti-cow IgG.…”
Section: Immunofluorescence and Confocal Fluorescence Microscopymentioning
confidence: 99%
“…Sodium dodecyl sulphate–polyacrylamide gel electrophoresis (SDS–PAGE) for the separation of LPS and lipid A was carried out in 12 and 15 % discontinuous gels in a Mini Protean II unit (Bio‐Rad, Richmond, CA, USA). The transfer of the antigens to nitrocellulose membranes was performed as previously described (Rojas et al., 1994). Briefly, the gels were electrotransferred in a semidry transblot cell (Bio‐Rad) for 15 min at 15 V. After blocking overnight at 4°C with PBS–0.05 % Tween 20–2 % casein, the membranes were incubated for 2 h at 37°C with sera diluted 1:500, followed by washing as above.…”
Section: Methodsmentioning
confidence: 99%
“…Because LPS is the major antigenic component of the outer membrane in Brucella , a large proportion of the humoral response of cattle is directed to LPS, particularly to its more exposed region, the O‐chain. However, little is known about the recognition of ‘deeper’ domains in the LPS molecule, such as the core oligosaccharide and lipid A (Rojas et al., 1994). In order to investigate the specificity of bovine sera to the different domains of B. abortus LPS, several immunochemical tests were performed with positive sera, and the results were evaluated considering previous findings on the epitopic distribution of the molecule.…”
Section: Introductionmentioning
confidence: 99%